Prevalence of Asymptomatic Rise in Troponin I in Hemodialysis Patients at a tertiary care hospital - German, Sidra; Waqar, Tajammul; Bhatti, Sajid; Rizwan, Anum; Mangi, Imran; Lashari, Sajid (Pakistan Journal of Kidney Diseases, 2024)
Objective: To determine frequency of asymptomatic rise in troponin-I among hemodialysis patients. To compare the mean of asymptomatic rise in troponin I between twice and thrice weekly hemodialysis patients. Methods: It is a Cross Sectional Study held in Sindh Institute of Urology and Transplantation outpatient dialysis department from June 25, 2020 to December 26, 2020 All patients of either gender age greater than 18-80 years undergoing hemodialysis via permanent angio-access without any history of shortness of breath and chest pain in preceding two weeks were consecutively enrolled. Information related to age, gender, causes of ESRD, duration of hemodialysis, date of last dialysis and date of sample collection was noted. Those whose troponin I was in cardiac range was admitted. Results: Of 127 patients, mean age was 38.17 ±14.75 years. There were 64 (50.4%) females and 63 (49.6%) males. Twice weekly hemodialysis was observed in 64 (50.4%) and thrice weekly in 63 (49.6%) patients. Mean troponin I level was 33.99 ±63.38 ng/ml. Raised troponin I level was found in 26 (20.50%) patients. The mean troponin I level among with twice weekly hemodialysis was 38.46 ±78.42 while among thrice weekly hemodialysis session was 29.45 ±43.27 (p-value 0.425). Conclusion: The frequency of asymptomatic rise in troponin-I was found to be 20.5% among hemodialysis patients. However, the mean difference of troponin I level with number of sessions showed insignificant difference.